The Effect of a New Ligation and Venipuncture Method on Vena Basilica Vessel - Yuanhong Mao; Xiaomei Huang; Hong Yang; Shu Zhou; Aihong Yuan; Gang Lin; Guiling Geng (Applied Bionics and Biomechanics)
Objective. This study evaluated the impact of a novel venipuncture method on vascular parameters of vena basilica to provide a new technical option for the clinical management of difficult venipuncture. Methods. 32 volunteers examined by ultrasound at the Medical Imaging Center of The First People’s Hospital of Nantong, Jiangsu province, from February 2020 to April 2020 were randomly selected. One hand of each patient was ligated with the traditional single tourniquet and the new ligation method for 20 seconds. Then, the distance between the left or right vena basilica and the skin and the diameter of blood vessels were measured by ultrasound. 98 patients with peripheral venipuncture difficulty who were examined by ultrasound of a third-grade hospital from April 2019 to March 2020 were selected and randomly divided into control group (n=49) and experimental group (n=49). The traditional method was used in the control group, and the new peripheral venipuncture was used in the experimental group. The success rate of single puncture, preparation time before puncture, time required for puncture operation, pain reaction during puncture, intravascular congestion after puncture, subcutaneous tissue injury, and vascular reuse rate after puncture were compared between the two methods. Results. The new ligation and puncture method increased the diameter of peripheral superficial vein vessels by 0.51±0.04 mm, and the change of vena basilica diameter was not significantly associated with gender and age of patient. The success rate of single puncture and the vascular reuse rate were significantly higher in the experimental group than in the control group, while the preparation time and venipuncture time, as well as the patient’s pain response, were significantly lower in the experimental group compared to the control group, and the intravascular congestion and subcutaneous tissue injury were lower. In addition, the mean satisfaction score of patients in the experimental group was higher than that of the control group. Conclusion. The new ligation and puncture method was an effective vena basilica dilation technique for filling the peripheral superficial veins, improving puncture success rate of peripheral difficult vein, and reducing patient pain, which was worth popularizing and applying in clinic.